Efficiency in the Programming and Financing of Social Protection - Sabbih, Mostafa Amir; Coudouel, Aline (World Bank, Washington, DC, 2021)
Social protection (SP) in Bangladesh is characterized by a large number of programs. Multiple agencies implement numerous interventions. To maximize the impact of social protection programs, it is critical to: (1) align the allocation of resources with national policies and strategies; (2) design programs that are able to reach their intended beneficiaries with adequate coverage and level of benefits; (3) ensure efficiency in programming and financing; and (4) ensure efficiency in the actual delivery of programs at the local level. This policy note analyses point (3), the processes of budgeting, programming, and reporting on SP budget, highlights areas where challenges remain, and proposes policy recommendations to address those.